ENGINEERING EDUCATION IN DIGITAL WORLD - V. G. Ivanov; A. A. Kaybiyaynen; L. T. Miftakhutdinova (Высшее образование в России, 2018)
The article highlights the challenges of global digital society and describes relevant problems discussed at the International Conference on Engineering Education in Budapest (Hungary) in September 2017. The authors focus on the contribution of Russian researchers to the development of engineering pedagogy and modern engineering staff training on the basis of the world trends of digital economy and online-learning development.